Small-Signal Analysis of Parallelly Connected Buck Converters and Nonlinear Droop Control Design for Ultra-Fast Transient Performance in DC Microgrids - Kapat, Santanu (2022 IEEE 1st Industrial Electronics Society Annual On-Line Conference (ONCON), 2022)
Majority of droop control methods in DC microgrid applications are primarily focused on steady-state voltage and/or current regulation requirements among interconnected DC-DC converters. Also, a standalone approach is often used, considering small-signal models, for analysis and design of individual DC-DC converters connected in series/parallel configurations in a DC microgrid. Considering a current mode controlled buck-derived DC microgrid, this paper presents small-signal analysis of multiple buck converters that are connected in parallel. Further, cross coupling effects are demonstrated among multiple parallel converters via DC bus. A decoupling control method is presented using small-signal models. Dynamic droop control objectives are identified to satisfy desired voltage regulation and/or current sharing requirements. Finally, considering a dynamic droop control method, a large-signal PI controller tuning is proposed in current mode interconnected buck converters. The proposed tuning can achieve near time optimal transient recovery in individual converters and would also satisfy desired power sharing even under varying power stage parameters. MATLAB simulation results are presented to demonstrate the usefulness of the proposed nonlinear controller tuning method. The proposed large-signal based tuning method can be extended to a more complex DC microgrid consisting of increasing number of parallel buck-derived DC-DC converters under current mode dynamic droop control.